2016
DOI: 10.1371/journal.pone.0149846
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of Alcohol Oxidase from Pichia pastoris

Abstract: FAD-dependent alcohol oxidases (AOX) are key enzymes of methylotrophic organisms that can utilize lower primary alcohols as sole source of carbon and energy. Here we report the crystal structure analysis of the methanol oxidase AOX1 from Pichia pastoris. The crystallographic phase problem was solved by means of Molecular Replacement in combination with initial structure rebuilding using Rosetta model completion and relaxation against an averaged electron density map. The subunit arrangement of the homo-octamer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 52 publications
(69 reference statements)
2
35
1
Order By: Relevance
“…suggested that Wat541 mimics the orientation of the substrate hydroxyl group as opposed to acting directly in the catalytic mechanism. This has also been suggested by other structural studies of oxidoreductase enzymes265051. It is stabilized by a hydrogen bond donor interaction from His447 and a hydrogen bond acceptor interaction from Glu36119.…”
Section: Resultssupporting
confidence: 67%
“…suggested that Wat541 mimics the orientation of the substrate hydroxyl group as opposed to acting directly in the catalytic mechanism. This has also been suggested by other structural studies of oxidoreductase enzymes265051. It is stabilized by a hydrogen bond donor interaction from His447 and a hydrogen bond acceptor interaction from Glu36119.…”
Section: Resultssupporting
confidence: 67%
“…Red stars indicate the absence of kinetic data. Abbreviations (and associated references for corresponding data) are as follows: Lac, laccase(380)(381)(382)(383); POD, peroxidase(380,(384)(385)(386)(387)(388); CDH, cellobiose dehydrogenase(102,(128)(129)(130)(389)(390)(391)(392); GOX, glucose oxidase(167,(393)(394)(395)(396)(397)(398); AAO, aryl alcohol oxidase(166,399,400); GDH, glucose dehydrogenase(401,402); AAQO, aryl alcohol quinone oxidoreductase(403); PDH, pyranose dehydrogenase(404)(405)(406)(407); AOX, alcohol oxidase(177,(408)(409)(410); P2O, pyranose 2-oxidase(181,(411)(412)(413); VAO, vanillyl alcohol oxidase(186,187); GLOX, glyoxal oxidase(170,<...>…”
mentioning
confidence: 99%
“…Notable exceptions are the highly radiation-sensitive carboxylate side chains of glutamate and aspartate [ 37 , 46 ] and surface-exposed side chains, mostly of lysines and a few arginines. Comparison with the very recent 2.35-Å crystal structure of AOX [ 18 ] (pdb 5hsa) shows a high correspondence between the two models with an RMSD of 0.58 Å for the C-α atoms and 1.12 Å for all atoms.…”
Section: Resultsmentioning
confidence: 72%
“…Although the peroxisomal crystal form of AOX can be easily grown in vitro , these crystals do not diffract X-rays to high enough resolution to determine the structure [ 13 , 15 ]. AOX in a different crystal form, grown in the presence of azide, diffracted to 2.7 Å resolution [ 16 ], but although the presence and orientation of the octamers in the asymmetric unit was established by electron microscopy [ 17 ], the structure was not solved until very recently [ 18 ]. Crystal structures are available for several other members of the GMC family: choline oxidase (CHOX) [ 19 ][ 20 ][ 21 ], aryl alcohol oxidase (AAOX) [ 3 ], glucose oxidase (GOX) [ 22 , 23 ], pyranose 2-oxidase [ 24 26 ], cellobiose dehydrogenase [ 27 ], cholesterol oxidase [ 28 ][ 29 ], and an hydroxynitrile lyase related to aryl alcohol oxidase [ 30 ].…”
Section: Introductionmentioning
confidence: 99%